Resilience as a Socially Embedded Process in Cervical Cancer Care: A Qualitative Study - Herdhana Suwartono; Juraid Abdul Latief; Achmad Herman; Muhammad Ryman Napirah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Cervical cancer continues to pose significant health and psychosocial challenges in low- and middle-income countries. This study aimed to explore how women with cervical cancer and their caregivers construct resilience in the face of illness, focusing on the roles of emotional, informational, and spiritual supports. By examining these dimensions, the study contributes to a deeper understanding of resilience as a socially embedded process shaped by cultural frameworks and clinical interactions. Methodology: A qualitative research design was employed, drawing on in-depth interviews with women diagnosed with cervical cancer and one caregiver at a referral hospital in Indonesia. Informants were selected purposively to capture diverse illness trajectories, and thematic analysis was applied to verbatim transcripts. Analytical rigor was ensured through triangulation, iterative coding, and interpretive synthesis. Results: Findings indicate that resilience is not a fixed personal trait but a negotiated and dynamic process. Emotional reassurance from family and colleagues, clear and compassionate communication by clinicians, and the grounding of experiences in spirituality and religious practices all facilitated adaptation and treatment adherence. At the same time, resilience revealed ambivalence: moralized expectations of being a “good patient” encouraged compliance but risked silencing distress, while some informants engaged in resistance through treatment hesitation or refusal. Interpreting these findings through subjectivation, psychological, and ecological lenses illustrates that resilience is discursively produced, individually enacted, and structurally conditioned. Conclusion: This study concludes that resilience in cervical cancer care is best understood as a culturally embedded and multi-layered phenomenon. Its implications underscore the need for context-sensitive psychosocial oncology practices that integrate family support, culturally grounded spiritual care, and dialogic communication. By situating Indonesian experiences within broader international debates, the research contributes new insights to global psycho-oncology scholarship and highlights avenues for future inquiry, including longitudinal research and the development of culturally validated assessment tools.